1988
DOI: 10.1002/bsl.2370060105
|View full text |Cite
|
Sign up to set email alerts
|

The effects of legislative reform on civil commitment admission rates: A critical analysis

Abstract: Many jurisdictions across North

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Recently, changes have been introduced to the Norwegian legislation, including a requirement of a lack of capacity to consent and for an exhaustive written justification for involuntary admission [ 12 ]. These changes could help reduce rates, although such an effect on coercion has not been consistent in other countries that have changed their legislation [ 120 – 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, changes have been introduced to the Norwegian legislation, including a requirement of a lack of capacity to consent and for an exhaustive written justification for involuntary admission [ 12 ]. These changes could help reduce rates, although such an effect on coercion has not been consistent in other countries that have changed their legislation [ 120 – 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…In considering the impact of ICC criteria, researchers have primarily focused on the "numbers admitted to inpatient care" and the "duration of hospitalizations" as indicators of "frequency" and "intensity" of utilization. Researchers have generally shown that the broadening of ICC criteria is associated with an immediate increase in admission rates which are sustained for at least 2 years [46]. When ICC criteria are narrowed to a dangerousness standard, 15 of 17 short-and long-term studies based on independent data sets showed increases in admissions followed by initial post-reform decreases [46].…”
Section: Icc Statutory Criteria Mental Health Inpatient Involvementmentioning
confidence: 99%
“…More than 25 studies that might have demonstrated a negative impact of the new laws were conducted in at least 16 North American jurisdictions 12. Most did show a decline in total involuntary admissions in the year following legislative change, but this was usually followed by a recovery in the admission rate over the subsequent years.…”
Section: The Origins and Impact Of The Dangerousness Criterionmentioning
confidence: 99%